Feasibility and preliminary safety of nitric oxide releasing solution as a treatment for bovine mastitis. (June 2018) - Regev, Gilly; Martins, James; Sheridan, Michael P.; Leemhuis, Jonathan; Thompson, James; Miller, Christopher
Abstract: Nitric oxide-releasing solution (NORS) is a liquid formulation that releases nitric oxide, a broad spectrum antimicrobial, single electron nitroxide radical. This solution was investigated as a potential antimicrobial treatment for bovine mastitis (BM). Three experiments were performed: a) NORS' effect on Staphylococcus aureus and Escherichia coli in an in vitro model; b) NORS' effect on milk obtained from dairy cows showing symptoms of clinical mastitis; and c) the consequences of administering NORS to healthy milking cattle using a dose-escalating in vivo study. Metabolite concentrations were estimated in their blood for methaemoglobin and nitrite; also, milk nitrite concentration and somatic cell count (SCC) were measured to study possible mammary gland inflammation following treatment. NORS lowered the bacterial concentration in all infected samples, in a time- and milk-diluted dependant fashion. Blood methemoglobin concentrations following treatment were all within the normal range for cattle. However, blood and milk nitrite concentrations increased initially but, during the next 24 h, returned to normal range, as did SCC, without any clinical signs of mammary gland inflammation. NORS, if shown to be effective, could be an alternative treatment for mastitis with a shorter clearance time. Highlights: NORS was an effective antimicrobial against bacteria associated with mastitis. NORS was found to be safe to animals, not causing any abnormal symptoms. Blood Methaemoglobin increased post treatment and return to baseline within 8 h. Milk nitrites were shown to increase but return to baseline within 24 h.